"You Start Feeling Old": Rock Musicians Reconciling the Dilemmas of Adulthood. (May 2013) - Ramirez, Michael
Using interview data from 38 musicians, this study examines the ways in which the transition to adulthood is complicated by aspirations to a nonstandard line of work. Musicians face a recurring set of obstacles as they move into adulthood and respond by enacting various tactics to reconcile these dilemmas. The "on-time" musicians do so by framing emerging adulthood as a time for exploration, while musicians in young adulthood regarded as "off-time" feel more pressure to disengage from musical careers. Those who persist are able to do so by successfully reframing the musician identity as congruent with adulthood. This research illustrates the challenges of attaining adulthood for those on nonstandard paths as well as the ways in which adulthood is achieved by contemporary young adults.